2023
DOI: 10.2460/ajvr.22.11.0191
|View full text |Cite
|
Sign up to set email alerts
|

Straight Egyptian Arabian skull morphology presents unique surgical challenges compared to the Thoroughbred: a computed tomography morphometric anatomical study

Abstract: OBJECTIVE The objective of this study was to compare the skull morphology of the Straight Egyptian Arabian (SEAR) to the Thoroughbred (TB), using computed tomography (CT) in the context of surgical procedures commonly performed on the equine head. ANIMALS Measurements relating to surgical considerations of the equine head were taken from 29 clinically normal adult horses (15 SEAR, 14 TB). PROCEDURES A clinical prospective study. Standing skull CTs were performed. Fourteen gross and 10 CT measurements were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
5
1
Order By: Relevance
“…Previous findings indicate that there is no significant difference in the lengths of the caudal or rostral maxillary sinuses between the 2 breeds. 8 While this is not directly comparable to the Mxa length in the present study, which was measured as the distance between the superior molar and superior premolar, it does suggest that the difference between the 2 breeds may be attributable to the SEAR having a shorter EtL distance. Again, while not directly comparable, it has been shown that absolute distances from the maxillary septal bulla to the rostral aspect of the cribriform plate are significantly shorter in SEAR compared to TB.…”
Section: Discussioncontrasting
confidence: 77%
See 4 more Smart Citations
“…Previous findings indicate that there is no significant difference in the lengths of the caudal or rostral maxillary sinuses between the 2 breeds. 8 While this is not directly comparable to the Mxa length in the present study, which was measured as the distance between the superior molar and superior premolar, it does suggest that the difference between the 2 breeds may be attributable to the SEAR having a shorter EtL distance. Again, while not directly comparable, it has been shown that absolute distances from the maxillary septal bulla to the rostral aspect of the cribriform plate are significantly shorter in SEAR compared to TB.…”
Section: Discussioncontrasting
confidence: 77%
“…Again, while not directly comparable, it has been shown that absolute distances from the maxillary septal bulla to the rostral aspect of the cribriform plate are significantly shorter in SEAR compared to TB. 8 It could be theorized that this may have an impact on the length of the EtL in the current study, potentially causing the SEAR to have a shorter EtL and thus a significantly greater Mxa/EtL ratio. However, further investigation is required to understand these differences in more detail.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations